EFEKTIFITAS BIOURINE DIPERKAYA DENGAN AGENS PENGENDALI HAYATI UNTUK PENGENDALIAN HAMA Spodoptera exiqua Hubner. (Lepidobtera: Noctuidae) PADA TANAMAN BAWANG MERAH LEMBAH PALU (Allium ascallonicum L.) - sujana, I gede arya; nasir, Burhanuddin; Rosmini, Rosmini (AGROTEKBIS, 2018)
This research aims wasto determine the effectiveness of biourin enriched with biological control (Trichoderma sp. and Beauveria sp.) insuppressing the development of S. exiquain Lembah Palu shallot (Allium ascalonicum, L.) plantation. The research was conducted in Sidera village Sigi Biromaru sub district, Sigi, Central Sulawesi province. This study used a randomized block design  with four treatments i.e. control (B0), biourin(B1), biourin mixed withTrichoderma sp. (B2), and biourin mixed withBeauveria sp. (B3). Each treatment had three replicates.The treatments were applied every week after observation on plant height, leaf number, seedling number and the intensity of S. exiqua attacks. The results showed that the treatments had significant effect on plant height, leaf number, and the number of seedlings. The plants grew in the control treatmentshowed lower plant height (23.58cm),less plant leaf number (19.46), and fewer tillers (3.43) compared to that in theB3 treatment which had plant height, leaf number, and tiller number were 32.64cm, 34.50 and 6.83, respectively.  The application of the treatments significantly reduced the the intensity of S. exiqua attacks.  It was found that the intensity attacks decreased from 17.78% under the control treatment to only 7.78% under the B3 treatment. Higher production was also found in the B3 treatment (35.43 g) than that in the control (20.53 g).